2022
DOI: 10.1002/cssc.202200352
|View full text |Cite
|
Sign up to set email alerts
|

Research Progress of Highly Efficient Noble Metal Catalysts for the Oxidation of 5‐Hydroxymethylfurfural

Abstract: This publication is part of a collection of invited contributions focusing on "Green Conversion of HMF". Please visit chemsuschem.org/collections to view all contributions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 169 publications
(176 reference statements)
0
13
0
Order By: Relevance
“…85 No DFF intermediate was found, demonstrating that the oxidative esterification of aldehyde preferentially proceeded on these catalysts. In a critical review, Xu et al 86 compared the mechanism and oxidation pathways of five noble metal catalysts (Au, Pt, Pd, Ru and Ag) on the HMF oxidation reaction in detail and discussed the effects of reaction conditions (such as temperature, pressure, time, etc. ) on the catalytic performance of the metal catalysts.…”
Section: Valorization Of Cellulosementioning
confidence: 99%
“…85 No DFF intermediate was found, demonstrating that the oxidative esterification of aldehyde preferentially proceeded on these catalysts. In a critical review, Xu et al 86 compared the mechanism and oxidation pathways of five noble metal catalysts (Au, Pt, Pd, Ru and Ag) on the HMF oxidation reaction in detail and discussed the effects of reaction conditions (such as temperature, pressure, time, etc. ) on the catalytic performance of the metal catalysts.…”
Section: Valorization Of Cellulosementioning
confidence: 99%
“…337 Despite the versatility of perovskites as precursors to bifunctional catalysts possessing metal-acid or metal-base functionality, there are no reports to date of perovskite supported catalysts for 5-HMF selective oxidation to FDCA. 338…”
Section: Esterification and Transesterificationmentioning
confidence: 99%
“…Mechanistic studies revealed that photogenerated electron–hole pairs, • O 2 – and 1 O 2 species all influenced the selective conversion of 5-HMF to DFF over MAPbBr 3 (Figure b) . Despite the versatility of perovskites as precursors to bifunctional catalysts possessing metal-acid or metal-base functionality, there are no reports to date of perovskite supported catalysts for 5-HMF selective oxidation to FDCA …”
Section: Perovskite Catalyzed Biomass Valorizationmentioning
confidence: 99%
“…In the last two decades, typical biomass-derived platform molecules including alcohols, [18][19][20][21] aldehydes, [22][23][24][25] acids, [26][27][28][29][30] esters, [31][32][33][34] phenols, 35,36 arenes, [37][38][39] and aromatic amines 40,41 have received intensive attention. These platform molecules that are obtained from cellulose, hemicellulose or lignin have been reported to be efficiently converted into a wide range of value-added chemicals and liquid fuels through various upgrading strategies.…”
Section: Introductionmentioning
confidence: 99%